Experimental Aerosol Inoculation and Investigation of Potential Lateral Transmission of Mycobacterium bovis in Virginia Opossum (Didelphis virginiana) - Karla A. Fenton; Scott D. Fitzgerald; Steve Bolin; John Kaneene; James Sikarskie; Rena Greenwald; Konstantin Lyashchenko (Veterinary Medicine International)
An endemic focus of Mycobacterium bovis (M. bovis) infection in the state of Michigan has contributed to a regional persistence in the animal population. The objective of this study was to determine if Virginia opossums (Didelphis virginiana) contribute to disease persistence by experimentally assessing intraspecies lateral transmission. One wild caught pregnant female opossum bearing 11 joeys (young opossum) and one age-matched joey were obtained for the study. Four joeys were aerosol inoculated with M. bovis (inoculated), four joeys were noninoculated (exposed), and four joeys plus the dam were controls. Four replicate groups of one inoculated and one exposed joey were housed together for 45 days commencing 7 days after experimental inoculation. At day 84 opossums were sacrificed. All four inoculated opossums had a positive test band via rapid test, culture positive, and gross/histologic lesions consistent with caseogranulomatous pneumonia. The exposed and control groups were unremarkable on gross, histology, rapid test, and culture. In conclusion, M. bovis infection within the inoculated opossums was confirmed by gross pathology, histopathology, bacterial culture, and antibody tests. However, M. bovis was not detected in the control and exposed opossums. There was no appreciable lateral transmission of M. bovis after aerosol inoculation and 45 days of cohabitation between infected and uninfected opossums.